The Effect of Capital Intensity, Inventory Intensity, Profitability, and Leverage on Tax Avoidance in Real Estate Companies - Febri Putri Nur Intan Sari; Dyah Ratnawati (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
The present study investigates how capital intensity, inventory intensity, profitability, and leverage influence tax avoidance in property and real estate firms listed on the Indonesia Stock Exchange during the 2022-2024 period. A quantitative methodological design is applied, utilizing the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach with SmartPLS 4 software assistance. Sample selection is conducted through purposive sampling, yielding 33 companies and a total of 99 observations. The analysis relies on secondary data collected from corporate annual financial statements. The results reveal that capital intensity, inventory intensity, and leverage do not have a significant impact on tax avoidance, implying that investment in fixed assets, the scale of inventory holdings, and the firm’s financing structure are not key determinants of tax avoidance behavior. Conversely, profitability exhibits a significant correlation with tax avoidance, implying that firms with higher profit levels show a greater tendency toward legally compliant tax efficiency practices. An R² value of 0.227 implies that 22.7% of the variability in tax avoidance can be attributed to the independent variables included in the model, while the remaining proportion is attributable to factors not captured in the study. These results imply that financial performance exerts a more prominent impact on tax avoidance behavior compared to the firm’s asset composition and financing structure.